Restoration of the Great Lakes : promises, practices, performances - Sproule-Jones, Mark, 1941- (desLibris. Books collection., 2002)
"The Great Lakes of North America are one of the world's most important natural resources. Home to more than 33 million Canadians and Americans, and the source of vast quantities of fish, hydroelectric energy, and usable water, they are also increasingly the site of severe environmental degradation and resource contamination. This study analyzes how well governmental and other stakeholders are addressing these critical problems." "Using original findings from surveys, interviews, and other documents, Mark Sproule-Jones looks at how various levels of government, particularly the bureaucracies of two national, one provincial, and eight state governments, are attempting to restore the environment in the Great Lakes. He examines the modest successes and major failures, identifying the kinds of institutions that promote sound decision making."--Jacket